EFEKTIVITAS PERKULIAHAN ONLINE DI MASA PANDEMI COVID-19 PADA MAHASISWA UAD WATES - Irsyaadul 'Ibaad; Unik Hanifah Salsabila; Muhammad Fatahillah; Adam Baustin Erlangga; Faisal Abyan Hanif (Jurnal Konseling Pendidikan Islam, 2021)
The Covid-19 outbreak provided surprises and also provided challenges for various educational institutions, including universities. The government has banned universities from conducting face-to-face lectures. The government has issued a policy for implementing temporary courses online (Ministry of Education and Culture Dikti Circular No.1 2020). All universities are required to be able to conduct online or online learning. This study aims to determine the effectiveness of online lectures during the Covid-19 Pandemic for UAD Wates. This research method uses descriptive analysis method through a survey with a google form questionnaire which is conducted online. The sample in this study were students of UAD Wates class of 2017, 2018, and 2020. The respondents in this study were 15 respondents. The effectiveness of online lectures during the Covid-19 Pandemic for students at UAD Wates was quite effective in preventing the transmission of the Covid-19 virus. However, the results of the study also show that online lectures have not been running effectively, because there are still lecturers who do not conduct online lectures. The learning method used is still dominant with assigning assignments to students so that many students are overwhelmed in doing coursework.